Pemberdayaan Masyarakat Melalui Program Kuliah Kerja Nyata (Kkn) Dalam Menjaga Ketahanan Pangan - Muhammad Zantoni; Pirmansyah; Minhajul Abidin; Cahya Ridhatunnisa; Deva Krisiawati; Rani Aprianti; Yuniatul Azmi; Sinta Dewi; Baiq Tsana’unnisak; Rasmiati; Hasbullah; Ria Hendriani (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Kelompok Wanita Tani (KWT) is a form of community empowerment that plays an important role in strengthening household food security. This article aims to describe the activities of establishing and mentoring a KWT conducted by students of the Community Service Program (Kuliah Kerja Nyata/KKN) from Universitas Qamarul Huda Badaruddin in Selebung Madani Village. The implementation method employed a participatory approach through socialization, training, and direct mentoring. The results of the program indicate the successful formation of an active KWT that utilizes home gardens for cultivating food crops and vegetables, as well as an increase in members’ knowledge and participation in supporting household food security.